2014
DOI: 10.1016/j.bbadis.2014.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of G protein-coupled receptor kinase 2 levels enhances cardiac insulin sensitivity and switches on cardioprotective gene expression patterns

Abstract: G protein-coupled receptor kinase 2 (GRK2) has recently emerged as a negative modulator of insulin signaling. GRK2 downregulation improves insulin sensitivity and prevents systemic insulin resistance. Cardiac GRK2 levels are increased in human heart failure, while genetically inhibiting GRK2 leads to cardioprotection in mice. However, the molecular basis underlying the deleterious effects of GRK2 up-regulation and the beneficial effects of its inhibition in the heart are not fully understood. Therefore, we hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
49
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 53 publications
5
49
0
Order By: Relevance
“…ERK axis activation could be part of the cardioprotective gene expression program initiated by GRK2 inhibition (12,13,41). Concomitantly, the expression of heart failure-promoting Pparg targets was blunted, and the appearance of the dysfunctional cardiac substrate metabolism was retarded.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ERK axis activation could be part of the cardioprotective gene expression program initiated by GRK2 inhibition (12,13,41). Concomitantly, the expression of heart failure-promoting Pparg targets was blunted, and the appearance of the dysfunctional cardiac substrate metabolism was retarded.…”
Section: Discussionmentioning
confidence: 99%
“…Because GRK2 inhibition also mediated the down-regulation of FASN-dependent cardio-lipotoxicity, patients with high morbidity and multiple risk factors may benefit from GRK2 inhibition. The additional insulin sensitivityenhancing activity of GRK2 inhibition (13,58) may further increase the value of such a strategy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the important role of this cascade in the heart, and the increased GRK2 cardiac levels detected in pathological conditions, we have studied insulin sensitivity in the cardiac tissue of 9 month-old WT mice compared to their GRK2+/-littermates. We have observed that GLUT4 translocation and glucose uptake as well as insulin-dependent Akt and p70S6K activation were impaired in WT but not in GRK2+/-animals [12] . Interestingly, although GRK2+/-mice displayed a larger cardiac area and cardiomyocyte diameter, they did not exhibit pathological cardiac hypertrophy.…”
Section: Research Highlightmentioning
confidence: 84%
“…Indeed, deletion of half the amount of GRK-2 gene expression systemically in mice protected against high-fat diet (HFD)-induced insulin resistance and obesity (GarciaGuerra et al 2010), as well as enhanced cardiac insulinstimulated Akt phosphorylation and glut-4 membrane translocation and reduced cardiac steatosis and fibrosis (Lucas et al 2014(Lucas et al , 2016. By contrast, overexpression of GRK2 in cardiomyocytes attenuated insulin-induced Akt phosphorylation and glut-4 membrane translocation (Ciccarelli et al 2011).…”
Section: :3mentioning
confidence: 99%